Gloves use and possible barriers – an observational study with concluding questionnaire - Imhof, Robert (GMS Hyg Infect Control, 2021)
Aim: The basic assumption of this study was that the use of medical non-sterile gloves represents a barrier to correct hand hygiene behaviour. The aim of this study was to examine this assumption and detect reasons for possible incorrect behaviour. Accordingly, the hypothesis is that peri-glove compliance is lower than hand-disinfection compliance. Methods: The study involved the direct observation of the use of non-sterile, single-use medical gloves in three different wards of a university hospital. Nursing staff and physicians were observed. After the observation period, the observed persons received a custom-designed questionnaire in order to test their self-assessment, knowledge as well as structural conditions relating to the use of gloves. The results were evaluated and compared with the observation data. Results: All employees disinfected their hands in 18.6% of cases before and in 65% of cases after the use of non-sterile gloves. Gloves were changed in the event of the indication for hand disinfection/change of gloves in 27.5% of cases. When changing gloves, the employees disinfected their hands in 47.2% of cases. The respondents assessed themselves as being significantly better than the observations revealed. The respondents are aware of the rules about hand disinfection before and after the use of gloves. However, it was less commonly known that gloves are not an absolute barrier to the transmission of bacteria. Conclusion: Non-sterile single-use gloves seem to be a barrier to hand disinfection. Solutions must be found in order to improve peri-glove compliance, in particular with regard to hand disinfection before and during the wearing of gloves. Alongside the mere transfer of knowledge, the use of non-sterile gloves with regard to the current structural conditions in everyday clinical practice should be critically scrutinised, questioned, tested and developed for the users through precise instructions.